Applying an Instrument for the Stratification of Patients with Community-acquired Pneumonia in the Emergency Department. - Luis Alberto Corona Martínez; Maria Caridad Fragoso Marchante; Iris González Morales; Dianelys Perla Sierra Martínez; Sandra Borroto Lecuna; Osmel Chávez Troya (Medisur)
Background: the stratification of patients is a very useful procedure in medical practice. Objective: To assess the implementation of an instrument for the stratification of patients with community-acquired pneumonia in the Emergency Department. Methods: A descriptive study was conducted at the General University Hospital of Cienfuegos. The instrument was applied to 394 (hospitalized or already discharged from the institution) with a diagnosis of community-acquired pneumonia between June 2009 and December 2010. As part of the assessment, indicators for process and results were used. Results: The instrument that has been developed is based on comprehensive clinical information and supported by complementary radiological information. It allows the classification of patients into six different stratifying layers. Of the 394 patients admitted because of pneumonia, more than 85% was stratified. The stratification was correct in 82% of them. There was a high rate of adherence to the suggested location on the instrument (99%). Adherence to antimicrobial therapy was of 73%. Patients with moderate pneumonia and a high probability of poor outcome (60%) predominated. The highest mortality was found in cases with severe pneumonia and little chance of recovery (74%). The overall mortality was 31%. Conclusions: Although susceptible of improvement, this tool is considered to be very useful for the decision making process when dealing with patients suffering from community-acquired pneumonia attended in the Emergency Department. It reduces hospitalization criteria variability and influences in-hospital patients’ location and antimicrobial therapy.